Spinal Tuberculosis: Diagnosis and Management - Rasouli, Mohammad R. (Korean Society of Spine Surgery, 2012)
The spinal column is involved in less than 1% of all cases of tuberculosis (TB). Spinal TB is a very dangerous type of skeletal TB as it can be associated with neurologic deficit due to compression of adjacent neural structures and significant spinal deformity. Therefore, early diagnosis and management of spinal TB has special importance in preventing these serious complications. In order to extract current trends in diagnosis and medical or surgical treatment of spinal TB we performed a narrative review with analysis of all the articles available for us which were published between 1990 and 2011. Althoug h the development of more accurate imaging modalities such as magnetic resonance imaging and advanced surgical techniques have made the early diagnosis and management of spinal TB much easier, these are still very challenging topics. In this review we aim to discuss the diagnosis and management of spinal TB based on studies with acceptable design, clearly explained results and justifiable conclusions.